Chemical sensors based on photonic colloidal crystals - A. A. Kozlov; A. S. Aksenov; V. A. Dvoretsky; V. R. Flid (Тонкие химические технологии)
Objectives. The paper analyzes the results of research into the formation of photonic crystal structures from polymer microspheres and the mechanisms of spectral shifts during selective reflection of non-monochromatic incident radiation from them in the visible and infrared light, as well as the use of polymer microspheres as sensors for detecting chemical substances having similar structures.Results. Research carried out at the Ya.K. Syrkin Department of Physical Chemistry in the Institute of Fine Chemical Technologies of the RTU MIREA is presented. Issues related to the detection of substances with similar chemical structure using sensors based on photonic crystals made of polystyrene microspheres 160–300 nm in size, are considered. Spectral shifts of the reflected radiation from the crystal surface are registered in the visible spectrum when substances in the liquid or gas phase are detected by the crystal surface.Conclusions. The method of electrophoretic deposition of colloidal particles in the form of polymeric microspheres on conducting surfaces can be used to create ordered structures over large areas. However, the detection of individual compounds by the optical method is impossible without controlling the kinetics of spectral shifts of reflected radiation from the surface of photonic colloidal crystals. The spectral characteristics of such radiation are directly related to the particle sizes that determine the period of the crystal lattice. The diffusion of chemical substances into a photonic crystal, which results in a swelling of the particles forming it and a shift in the spectrum of reflected radiation, is determined by a change in the period of the crystal lattice due to a change in the size of these particles A kinetic model of swelling polymer microspheres, which describes the diffusion of substances into porous polymer particles, is proposed. An excess amount of substance deposited on the surface of a photonic crystal above the limit is shown to lead to its degradation, which is manifested in the “fading” of the crystal surface and the concomitant disappearance of narrow peaks of reflected radiation.